PEMANFAATAN LIMBAH PADATAN LEM KAYU LAPIS PT AKG MENJADI BAHAN BAKU ECOBRICK UNTUK FURNITUR - adiputra, anggara (Jurnal Teknologi Infrastruktur, 2024)
AKG is a company operating in the plywood production sector located in West Kalimantan. AKG plywood production process leaves a lot of glue solid waste which is still a problem. PT The aim of this research is to utilize plywood glue solid waste as raw material for ecobricks to make furniture (chairs and tables and stools). This research uses quantitative methods with interview and observation data collection methods. The results of this research are that plywood glue solid waste can be used as ecobricks and can be used as chairs and stools. One chair and stool table can utilize 18.9 kg of waste glue solids, and can produce 137 ecobricks per year, thereby reducing 7.25% of solid glue waste per day for a 1500 ml bottle volume.